Islamic Perspective on Importance of Breastfeeding: Two Case Reports - Mokhtar, Nurhawa; Sulaiman, Fatin Syuhadah; Kusumawardani, Anisa; Hidayat, Taufiq (IIUM Medical Journal Malaysia, 2018)
Breast milk contains all basic nutrition needed by a child. Exclusive breastfeeding is recommended to all infants in their first 6 months of life. Infants who had been exclusively breastfed have a better health status compared to infants who were introduced with mixed feeding in their early life. Exclusive breastfeeding not only gives benefits to the child, but also to the mother. In infants it offers protective mechanism in lowering risk of gastrointestinal infection and promotes bonding between the mother and the child. The first case was a 2 years and 7 months old girl who was admitted to Hospital Tengku Ampuan Afzan Kuantan due to acute gastroenteritis with some dehydration. She had been admitted a month earlier due to pneumonia. She was breast fed exclusively for 3 months after she was born. Formula feeding was started after she turned 4 months old.. The second case was a 1 year and 4 months old boy who was hospitalized due to acute bronchiolitis. He was not breast fed due to no milk production. Islam views childhood as a critical phase in molding an individual. Parents have been entrusted by Allah to observe and fulfill the rights of the children in providing a conducive environment for them to develop and grow. A good healthcare and proper nutrition are among the child’s rights that need to be filled by the parents. Islam emphasizes the importance of breastfeeding up to 2 years old as a way in providing good nutrition. Islam also provides solution for mothers who are unable to breastfed their child by adopting wet mother. Parents are responsible in providing good health and nutrition for their children. Breastfeeding is also highly encouraged by Islam because it provides medical benefits for both mother and children.